Per una pianificazione "a misura" di territorio Regole insediative, beni comuni e pratiche interattive - Perrone, Camilla (Territori, 2011)
The text proposes several approaches for reflection on the subject of the governance of territorial consumption, addressing two critical issues: the dimensioning of planning and the concept of territory as a common good. The latter is understood as the outcome of cooperative behaviour and interactive practices aimed at recognition of the value of the places and the definition of rules of settlement for the protection of increasingly scarce collective resources. Exploring the relations between the limits of efficacy of the mechanisms for dimensioning the plans and responsibilities of the policies for governance of the territory - increasingly torn between public and private interests and not sufficiently "shared" - the book offers food for thought on the role of a "territorial-size" type of planning in the acknowledgement and management of the common goods.